The VISIR Implementation Process at IFSC - problems, obstacles and solutions - Schlichting, Luis (2018)
In recent year, the use of remote laboratories applied to teaching has been more frequent in several educational institutions around the world. The benefits on the learning process are easy to verify. In addition, remote laboratories bring in their application, operational advantages associated to component inventory, equipment maintenance, security, and others practical issues. Considering this, it is intuitive that the implantation of a remote laboratory and its use is easily recognized and accepted by the users, namely, students and teachers. This paper aims to present the obstacles and advantages observed in the implantation of the virtual laboratory VISIR (Virtual Instruments Systems in Reality) at Federal Institute of Santa Catarina - IFSC, as well as the obtained results.